Negative rumination in social anxiety: A randomised trial investigating the effects of a brief intervention on cognitive processes before, during and after a social situation. (June 2017) - Modini, Matthew; Abbott, Maree J.
Abstract: Background and objectives: According to cognitive models of Social Anxiety Disorder (SAD), negative rumination is a key maintaining factor in the vicious cycle of social anxiety. However, there is a scarcity of research investigating treatment effects on rumination in social anxiety, as well as other key cognitive variables. The current study aimed to determine the effectiveness of a brief intervention on a range of cognitive processes, most notably negative rumination. Additionally, predictors of negative rumination and state anxiety are also investigated. Methods: Participants with a diagnosis of SAD were randomly allocated to an intervention (n = 24) or control group (n = 23). Participant's initially completed trait and state based measures with the intervention group also completing a brief cognitive intervention. One-week later participants completed state anxiety and cognitive measures before and after a speech task. Finally, one-week post-speech task participants completed further trait and state based measures. Results: While the brief cognitive intervention had positive effects on some of the cognitive processes measured at different time points of the study, levels of negative rumination remained stable. Predictors of negative rumination and state anxiety were consistent with cognitive models of SAD. Limitations: The brief nature of the intervention and temporal stance of the intervention (delivered one-week before the speech) may have impacted outcomes. Conclusions: Cognitive technique can potentially impact a range of key processes that maintain SAD, however, more powerful and tailored interventions are needed that address the different processes at play before, during and after a social situation for socially anxious individuals. Highlights: Effect of a brief cognitive intervention on cognitive processes is investigated. Negative rumination is an enduring process that requires tailored interventions. There are likely different predictors for each stage of the social situation.